Apigenin Ameliorates Dyslipidemia, Hepatic Steatosis and Insulin Resistance by Modulating Metabolic and Transcriptional Profiles in the Liver of High-Fat Diet-Induced Obese Mice - Jung, Un Ju (Nutrients, 2016)
Several in vitro and in vivo studies have reported the anti-inflammatory, anti-diabetic and anti-obesity effects of the flavonoid apigenin. However, the long-term supplementary effects of low-dose apigenin on obesity are unclear. Therefore, we investigated the protective effects of apigenin against obesity and related metabolic disturbances by exploring the metabolic and transcriptional responses in high-fat diet (HFD)-induced obese mice. C57BL/6J mice were fed an HFD or apigenin (0.005%, w/w)-supplemented HFD for 16 weeks. In HFD-fed mice, apigenin lowered plasma levels of free fatty acid, total cholesterol, apolipoprotein B and hepatic dysfunction markers and ameliorated hepatic steatosis and hepatomegaly, without altering food intake and adiposity. These effects were partly attributed to upregulated expression of genes regulating fatty acid oxidation, tricarboxylic acid cycle, oxidative phosphorylation, electron transport chain and cholesterol homeostasis, downregulated expression of lipolytic and lipogenic genes and decreased activities of enzymes responsible for triglyceride and cholesterol ester synthesis in the liver. Moreover, apigenin lowered plasma levels of pro-inflammatory mediators and fasting blood glucose. The anti-hyperglycemic effect of apigenin appeared to be related to decreased insulin resistance, hyperinsulinemia and hepatic gluconeogenic enzymes activities. Thus, apigenin can ameliorate HFD-induced comorbidities via metabolic and transcriptional modulations in the liver.